Characterisation of two putative rhomboid proteases in Shigella sonnei physiology and pathogenesis. - Liu, G (2018)
Shigella sonnei is a human-specific pathogen and a major cause of bacillary dysentery. Rhomboids are evolutionarily conserved serine intramembrane proteases that control a variety of important cellular processes, including regulating apoptosis in mammals, development in Drosophila, and invasion of eukaryotic parasites. However, functions of bacterial rhomboids remain largely unexplored. This work identified two active rhomboids: GlpG and Rhom7, in S. sonnei. Rhom7 possesses a novel domain composition among rhomboids characterised so far, consisting of seven transmembrane domains (TMDs) and a putative C-terminal WD40 domain. However, neither the 7th TMD nor the C-terminal domain is required for the proteolytic activity of Rhom7. To identify physiological substrates of GlpG and Rhom7, the cleavage propensity of TMDs derived from all predicted type I & III membrane proteins in S. sonnei were assessed. Candidate substrates were further validated by testing the cleavage of the full-length substrates by GlpG and/or Rhom7, revealing that HybA and FdoH are physiological substrates for GlpG, and that HybA and FdnH are substrates for Rhom7 but only when Rhom7 is expressed from a plasmid. Further analyses of these substrates revealed that they are all components of multi-protein respiratory complexes (HybA from hydrogenase-2, FdoH from formate dehydrogenase-O, and FdnH from formate dehydrogenase-N). I propose that their cleavage by rhomboids follows a ‘complex protection’ model, which states that only the uncomplexed substrates are cleaved by rhomboids, while the substrates residing in their native complexes are protected. As rhomboids are known to display propensity to cleave TMDs with low helical stability. I proposed that discrimination of uncomplexed and complexed substrates is likely to be mediated by the presence of helix-destabilising residues in the substrate TMDs, which render uncomplexed substrates prone to rhomboid cleavage while the stability of substrate TMDs is maintained by packing with TMDs from their binding partner(s) in the complex. Consistent with that, we identified helix-destabilising proline residues in HybA, FdoH, and FdnH. Moreover, substitutions of these residues with alanine abolished rhomboid cleavage regardless of complex integrity. These findings lead to the proposal that rhomboids might act as a quality control mechanism scrutinising membrane complex integrity, whose role might only become important under stresses.